Advanced Stretchable Photodetectors: Strategies, Materials and Devices. Issue 13 (4th January 2023) - Bai, Xinyao; Gao, Wanxiao; Cai, Yunpeng; Bai, Zhenxu; Qi, Yaoyao; Yan, Bingzheng; Wang, Yulei; Lu, Zhiwei; Ding, Jie
Abstract: Past decades have witnessed the generation of new stretchable photodetectors in electronic eyes, health sensing, wearable devices, intelligent monitoring and other fields. Stretchable devices require not only outstanding performance but also excellent flexibility, adaptability and stability. Innovative strategies have been proposed to realize the stretchability of devices. In addition, novel functional materials including zero‐dimensional nanomaterials, one‐dimensional inorganic nanomaterials, two‐dimensional layered materials, organic materials, and organic‐inorganic composite materials with excellent properties are emerging to continuously improve the performance of devices. Here, the recent research progress of stretchable photodetectors in terms of both various design methods and functional materials is outlined. The optical performance and stretchable properties are also comprehensively reviewed. Finally, a summary and the challenges associated with the application of stretchable photodetectors are presented. Abstract : A bit of a stretch : This review lays out the most recent developments in stretchable photodetectors, involving distinct design methods to realize stretchability, various novel function materials selected for photoelectric conversion and excellent properties of stretchable photodetectors.